Establishing Harmony and Social Awareness in Religious Diversity - Muhammad Dachlan (Asian Social Work Journal, 2023)
This article presents issues related to harmonization and social awareness in religious diversity in Indonesia. Maintaining religious harmony is the responsibility of the state and its people. Moreover, Indonesia is a country with people who have several religions and beliefs. Based on Pancasila, people try to maintain harmony with their social awareness in tolerance for practicing their respective religions. However, there are still ripples in this harmony. Several cases in the name of religion occurred. The state intervenes with regulations, religious leaders, community leaders, government and community members intervene to resolve them. Several research results found that religious harmony still leaves many problems. Models of religious relations that have not completely dissolved, prejudice still appears and remain within the framework of the dominance of the majority group. Respect for differences, tolerance, dialogue and communication, cooperation, and solidarity, overcoming prejudice and discrimination are ways to maintain harmony and social awareness in religious diversity.